Leveraging cover crop functional traits and nitrogen synchronization for yield-optimized waxy corn production systems - Sun, Mengjing; Zhang, Long; Zhou, Jiangkuo; Liu, Ziping; Peng, Cong; Jia, Zechen; Lv, Yanjie; Wang, Yongjun (Frontiers in Plant Science, 2025)
ContextProlonged monoculture of waxy corn (Zea mays L. var. ceratina Kulesh) exacerbates soil nutrient depletion and compromises soil structural integrity, concomitant with underutilization of photosynthetically active radiation (PAR) resources.ObjectiveImplementing cover cropping post-harvest of waxy corn can utilize residual environmental resources for soil quality improvement. Nevertheless, the agronomic consequences of this practice on canopy architecture optimization and resource allocation dynamics in subsequent growing seasons require systematic elucidation.MethodsThe regionally adapted cultivar Wannuo 2000 (W67×W68), predominantly cultivated in northeastern China, was employed for canopy characterization. Three experimental treatments were established, including waxy corn continuous monoculture control (CK), shamrock (Trifolium pratense L.) rotation cropping after waxy corn harvest (ZT) and rapeseed (Brassica napus L.) rotation cropping after waxy corn harvest (ZB). Each treatment incorporated five nitrogen (N) application gradients (0, 60, 120, 180, 240 kg N ha−¹) arranged in randomized complete block design (RCBD) with triplicate plots.ResultsCover crops integration significantly enhanced waxy corn productivity. Mean yields for ZT and ZB systems during 2022–2023 demonstrated 20.74% (8.88 ± 2.50 Mg ha−1) and 22.26% (8.99 ± 3.12 Mg ha−1) increases respectively compared to CK. Remarkably, under 25% N reduction scenarios, ZT and ZB achieved 15.25% (44.58 ± 6.28%) and 20.67% (46.68 ± 7.15%) improvements in nitrogen use efficiency (NUE) relative to conventional practice. The path analysis revealed synergistic interactions between cover crop incorporation and N management mediated through canopy structural optimization. Specifically, enhanced leaf area index (4.56 ± 0.69 m² m−²) and elevated pre-silking canopy N content (132.61 ± 26.33 g N plant−1) collectively drove post-silking biomass accumulation (134.88 ± 26.85 g plant−1) and N remobilization efficiency.ConclusionThe integrated cover crop-nitrogen reduction system enhanced both yield and NUE relative to monoculture benchmarks, demonstrating dual benefits in environmental conservation and agricultural productivity enhancement.ImplicationThis study establishes a theoretical framework and provides empirical evidence for the sustainable intensification of waxy corn production systems.